MENYINGKAP CINTA KASIH ALLAH PASCA TRAGEDI SITUBONDO 10 OKTOBER 1996 DALAM PERSPEKTIF TEKS NABI YOЁL 2:23-27 - Lamatokan, Yohanes Victor Baro Bitan; Permiro, Bonifacio Gendis (Lembaga Penelitian STKIP Widya Yuwana, 2024)
This research examines the efforts to capture God's love after the tragedy of the Situbondo riots, East Java, on October 10, 1996. The people of Situbondo and even the whole of Indonesia were shocked by the destruction and burning of 24 churches in the Situbondo area. The destruction and burning of churches in Situbondo began with the trial of Mohammad Soleh (Muslim). Soleh was a young man accused of spreading heresy and insulting the Islamic teachings of K.H. As'sad Syamsul Arifin, who is highly respected by the people of Situbondo. The court verdict that was too light for the masses caused Situbondo to become a sea of fire. This research uses a qualitative approach with a literature study. The theoretical framework used is the story of the Prophet Joel in his letter (Yl 2:23-27) about God's love for the Israelites after experiencing various disasters and other supporting sources. The results showed that the value of love was realized through the initiative of the Christian community (both Catholics and Protestants) by building dialogue between the two camps, both the majority group (Islam) and the minority group so as to create a tolerant situation between the two and thus, the relationship that had been tenuous could be restored.